STUDY OF PHOTODIODE STRUCTURES IN THE GALLIUM ARSENIDE-CADMIUM SULFIDE SYSTEM - Gaibov A. G.; Mirkamilova M. S.; Juraev U. E. (American Journals, 2024)
It is shown in this work that in a two barrier photodiode structure with a common modulated base region, the spectral characteristics for the cases of blockable p-n-hetero- (pGaAs-nCdS) and metal-semiconductor (m-pGaAs) junctions can have an identical form, where the formation mechanism is determined by the processes, occurring in the space charge regions located mainly in the common (pGaAs) region.
Keywords: Photosensitiveity, gallium arsenide, double-barrier structure, saturation currents, current-voltage characteristic.